Greater New York 2010 : MoMA PS1 and The Museum of Modern Art - Biesenbach, Klaus; Butler, Connie; Wakefield, Neville ([S.l.] : MoMA PS1, 2010)
Abeles, Michele ; Adamo, David ; Arakawa, Ei ; An Atlas of Radical ; Auerbach, Tauba ; Bader, Darren ; Brätsch, Kerstin ; Brooks, David ; The Bruce High Quality ; Chruchman, Leidy ; Cohen, Deville ; Condon, Brody ; Considine, Caleb ; Cordova, William ; Delusional Downtown ; DETEXT ; Eilers, Debo ; Evans, Franklin ; Frazier, LaToya Ruby ; Fried, Zipora ; Gordon, Daniel ; Halpern, Tamar ; K8 Hardy ; Hartung, Tommy ; Hayes, Sharon ; Horvat, Vlatka ; Hoyt, Matt ; Hubbard, Alex ; Kerlin, Alisha ; Liz Magic Laser ; Lawson, Deana ; Ledare, Leigh ; Leventhal, Dani ; Linzy, Kalup ; Madani; Tala ; Mauss, Nick ; McNamara, Ryan ; Miko, Dave ; Mogharabi, Amir ; Moyer, Sam ; Muhly, Nico ; Newsome, Rashaad ; Nurre, Dominic ; O'Connell, Brian ; O'Malley, Alice ; Overton, Virginia ; Pendleton, Adam ; Petschnig, Maria ; Prekop, Zak ; Randall Weeks, Ishmael ; Ratman, Gilad ; Raven, Lucy ; robbinschilds ; Robertson, Mariah ; Röder, Adele ; Roysdon, Emily ; Sasamoto, Aki ; Sherry, David Benjamin ; Shirreff, Erin ; Simmons, Xaviera ; Steiner, A.L. ; Subrin, Elisabeth ; Willis Thomas, Hank ; Tsabar, Naama ; van der Werve, Guido ; Ventur, Conrad ; Yao, Amy ; Yolaçan, Pinar
Greater New York, MoMA PS1 and The Museum of Modern Art, Long Island City, NY, May 24 - October 18, 2010
boek